Biomass production, soil properties and economics under silvipastoral system in degraded lands of semi-arid region of India - Rai, P.; Yadav, R.S.; Kareernulla, K.; Singh, U.P.; Singh, R. (Indian Journal of Agroforestry, 2020)
An investigation consisting of three MPTs viz. Acacia nilotica var cupressiformis, Dalbergia sissoo and Hardwickia binata in a silvipastoral system was carried out at research farm, National Research Centre for Agroforestry, Jhansi during 1992-2001 to study growth and productivity of the system, soil enrichment and economic returns. Among MPTs, D. sissoo attained highest growth parameters. Pruning of MPTs resulted into decrease in height, collar diameter (cd), diameter at breast height (dbh) and canopy spread. D. sissoo gave 0.36 t ha-1 yr-1 of leaf fodder and 1.18 t ha-1 yr-1 fuelwood followed by H. binata. Fourth year onwards, pasture production decreased significantly under different MPTs based silvipastoral system with maximum decrease in D. sissoo as compared to pasture alone (6.66 t ha-1 yr-1. Irrespective of MPTs, pruning resulted an increase in understorey pasture production. Compared to pasture alone, D. sissoo based silvipastoral system yielded higher returns foltowed by H. binata based system as compared to pasture alone (B: C ratio1.91).